Ergonyms of multiethnic city (based on city objets names of Kharkiv) - Мораді, Арезу (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 1970)
The article covers the last two decades topical issue of city objects nomination caused by an active development of nomination processes. Lexico-semantic methods of emporonyms and trapesonyms formation are described, questions of multilingual ergonyms coexistence in the multiethnic city are considered, the regional specifics of trade enterprises and public catering enterprises of Kharkiv is elicited as well.